Legal Protection of Customary Land Control by Communities through the Implementation of Agrarian Reform in Ternate City - Nurul Ayni; Husen Alting; Suwarti Suwarti (Jurnal Indonesia Sosial Sains, 2025)
This study explores legal issues surrounding the protection of customary land ownership through the implementation of agrarian reform in Ternate City. Existing legal frameworks, particularly the Basic Agrarian Law, remain insufficient in providing explicit recognition and legal protection for customary land that continues to exist without formal documentation. This research identifies areas of customary land in Ternate that have not been registered or recognized with formal ownership rights and examines the position of customary land ownership from the perspective of legal protection theory. The findings reveal that agrarian reform has had limited impact in securing customary land rights due to the absence of legal clarity and institutional support. Moreover, the National Land Agency's current policy strategies have not effectively integrated mechanisms to acknowledge and register customary land claims. The lack of harmonized regulations contributes to legal uncertainty and hinders the realization of equitable land rights. Therefore, this paper emphasizes the urgent need for a more comprehensive regulatory framework that ensures the legal recognition and protection of customary land within the agrarian reform agenda. This will contribute to stronger legal certainty, social justice, and the preservation of indigenous communities' land rights in Ternate City.